PENENTUAN KLORAMFENIKOL DALAM DAGING AYAM BROILER DENGAN METODE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) - Panggabean, Aman Sentosa (Universitas Trunojoyo Madura, 2012)
Determination of chloramphenicol on broiler meat in the traditional market by using High-Performance Liquid Chromatography (HPLC) method has been done. The optimal of result determination to obtain, the HPLC system has been optimized for the important parameters are a composition of the mobile phase, injection sample volume, flow rate, and even pH. The result of research shown that the optimum conditions to obtain from the research are a composition of mobile phase methanol: water (80: 20), injection sample volume 5 μL, flow rate 0.5 mL/minute and eluent pH are 6 has been achieved. The analytical performance of the method has been optimized and gives a good performance which shown with reproducibility of this method as the coefficient of variation percentage (% CV) was 0.2198 %, limit of detection was 0.1051 mg/L, and % recovery for the chicken meat sample with 3 different samples more than 95 %. This result showed this method capable of an application for the routine analysis of the determination chloramphenicol content in samples